ProSES Symposium - exploring into chemical engineering processes - UMP, PNC (2019)
More than 70 people attended the Process Systems Engineering and Safety (ProSES) Symposium 2019 organised by Process Systems Engineering and Safety Research Group, Faculty of Chemical and Process Engineering Technology (FTKKP). The participants comprised academicians, industry experts and UMP students. Themed, ‘Process Modelling and Simulation towards Industrial Revolution (IR 4.0)’, the symposium was held at Vistana Hotel in Kuantan on September 13, 2019.